Magnetic excitations and absence of charge order in the van der Waals ferromagnet Fe4.75GeTe2 - V. K. Bhartiya; T. Kim; J. Li; T. P. Darlington; D. J. Rizzo; Y. Gu; S. Fan; C. Nelson; J. W. Freeland; X. Xu; D. N. Basov; J. Pelliciari; et al. (npj Quantum Materials)
Abstract Understanding the ground state of van der Waals (vdW) magnets is crucial for designing devices leveraging these platforms. Here, we investigate the magnetic excitations and charge order in Fe4.75GeTe2, a vdW ferromagnet with ≈ 315 K Curie temperature. Using Fe L 3-edge resonant inelastic X-ray scattering, we observe a dual nature of magnetic excitations, comprising a coherent magnon and a broad non-dispersive continuum extending up to 150 meV, 50% higher than in Fe2.72GeTe2. The continuum intensity is sinusoidally modulated along the stacking direction L, with a period matching the inter-slab distance. Our results indicate that while the dual character of the magnetic excitations is generic to Fe-Ge-Te vdW magnets, Fe4.75GeTe2exhibits a longer out-of-plane magnetic correlation length, suggesting enhanced 3D magnetic character. Furthermore, resonant X-ray diffraction reveals that previously reported ±(1/3, 1/3, L) peaks originate from crystal structure rather than from charge order.